295 Regression Analysis to Predict the Impact of Dietary Neutral Detergent Fiber on Carcass Yield. (10th April 2018) - Soto, J A; Tokach, M D; Dritz, S S; Goncalves, M A D; Woodworth, J C; DeRouchey, J M; Goodband, B D
Abstract: Research has shown that carcass yield is reduced when feeding DDGS or other ingredients with high neutral detergent fiber (NDF). Considering the financial implications of changing carcass yield, the objective of this project was to develop a regression equation to estimate carcass yield from dietary NDF withdrawal strategies. Data from 8 trials (43 observations) originated from 5 journal articles, 2 theses and 1 technical memo were used to develop the regression equation. All trials applied treatments to mixed-sex pens. Treatment diets of each trial were reformulated to obtain nutrient content using the NRC ingredient library. Composition of experimental diets was used to calculate NE (kcal/kg), CP (%), crude fiber (CF [%]), NDF (%), and ADF (%) in the last two dietary phases. The PROC GLIMMIX procedure of SAS (SAS Institute, Inc., Cary, NC) was used to develop regression equations. The model was determined using a step-wise selection procedure starting with manual forward selection through individual predictor variables, with a statistical significance at P < 0.05 used to determine inclusion of terms in the final model. The regression analysis showed that number of days in the withdrawal period (WP; P = 0.011), NDF level in the dietary phase prior to the final phase (NDF1; P = 0.001), NDF level in the last dietary phase before marketing (NDF2; P < 0.001), and the interaction between NDF2 and WP (NDF2 × WP; P = 0.010) were the most important variables in the dataset to predict carcass yield. The resulting regression equation was carcass yield % = 0.03492 × WP (d) – 0.05092 × NDF1 (%) – 0.06897 × NDF2 (%) – 0.00289 (NDF2 (%) × WP (d)) + 76.0769. As expected, high levels of NDF had a negative impact on carcass yield. Increasing the length of the withdrawal period improved carcass yield; however, the effect of withdrawal period was dependent on the level of NDF2, as indicated by the interaction term. Carcass yield reduction from feeding high-fiber ingredients results from an increase in the weight of intestinal contents, and the increase in gut fill is a result of the type of fiber in the ingredients. Neutral detergent fiber has been shown to result in digestive contents to swell in the by absorbing water thus increasing the fecal volume in the large intestine. In conclusion, the equations herein provide an estimation of the impact of dietary NDF on carcass yield.